The dual systems model: Review, reappraisal, and reaffirmation. (February 2016) - Shulman, Elizabeth P.; Smith, Ashley R.; Silva, Karol; Icenogle, Grace; Duell, Natasha; Chein, Jason; Steinberg, Laurence
Highlights: Evidence related to the dual systems model of adolescent risk taking is reviewed. The review encompasses both the psychological and neuroimaging literatures. Recent findings (since 2008) generally support the dual systems model. Recommendations are made for future research directions. Abstract: According to the dual systems perspective, risk taking peaks during adolescence because activation of an early-maturing socioemotional-incentive processing system amplifies adolescents' affinity for exciting, pleasurable, and novel activities at a time when a still immature cognitive control system is not yet strong enough to consistently restrain potentially hazardous impulses. We review evidence from both the psychological and neuroimaging literatures that has emerged since 2008, when this perspective was originally articulated. Although there are occasional exceptions to the general trends, studies show that, as predicted, psychological and neural manifestations of reward sensitivity increase between childhood and adolescence, peak sometime during the late teen years, and decline thereafter, whereas psychological and neural reflections of better cognitive control increase gradually and linearly throughout adolescence and into the early 20s. While some forms of real-world risky behavior peak at a later age than predicted, this likely reflects differential opportunities for risk-taking in late adolescence and young adulthood, rather than neurobiological differences that make this age group more reckless. Although it is admittedly an oversimplification, as a heuristic device, the dual systems model provides a far more accurate account of adolescent risk taking than prior models that have attributed adolescent recklessness to cognitive deficiencies.